Yes, you are correct. 2x X=-3 2(-3) to the fourth power *you just plug in the x value. multiply 2 and -3 and that answer to the fourth power* also writing it like this 2(-3) and 2 x -3 basically mean the exact same thing...to multiply, but assuming you are in algebra you should write it out like this 2(-3) to the fourth power.
Is it 2x^4 or (2x)^4 !? Because if it is as the first one (the power is raised only on x), then it will be 2(-3)^4 = 2(81) = 162 IF it is as the second one (the power is raised on the whole function), then it will be (2 x -3)^4 = (-6)^4 = 1296